2015
DOI: 10.1002/pd.4685
|View full text |Cite
|
Sign up to set email alerts
|

Routine use of array comparative genomic hybridization (aCGH) as standard approach for prenatal diagnosis of chromosomal abnormalities. Clinical experience of 1763 prenatal cases

Abstract: The present study indicates that routine implementation of aCGH offers an incremental yield over conventional karyotype analysis, which is also present in cases with 'milder' indications, further supporting its use as a first-tier test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
19
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 31 publications
4
19
2
Order By: Relevance
“…Our results showed a higher percentage of VOUS in comparison to reported studies, where the detection rate ranged from 0.5 to 1.7% [Brady et al, 2014;Papoulidis et al, 2015]. This discrepancy may be due to (a) VOUS definition, considering that some groups do not report rearrangements containing no genes [Brady et al, 2014]; (b) array resolution (e.g.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Our results showed a higher percentage of VOUS in comparison to reported studies, where the detection rate ranged from 0.5 to 1.7% [Brady et al, 2014;Papoulidis et al, 2015]. This discrepancy may be due to (a) VOUS definition, considering that some groups do not report rearrangements containing no genes [Brady et al, 2014]; (b) array resolution (e.g.…”
Section: Discussioncontrasting
confidence: 55%
“…In the recent years, about 20 studies have examined the potential impact/pathogenicity of CNVs in fetal malformations in a prenatal diagnostic setting or after terminations of pregnancy [de Wit et al, 2014;Papoulidis et al, 2015;Srebniak et al, 2015]. The proportion of clinically relevant findings is highly variable (from 4.3 to 18%) [de Wit et al, 2014;Papoulidis et al, 2015;Srebniak et al, 2015], reaching 24% with our study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It has been previously reported that the screen positive group of combined testing includes cases with abnormalities that were not initially targeted and that are incidentally detected, such as other trisomies, sex aneuploidies, deletions, duplications, mosaicisms and others, and these defects accounted for about 10% of all aneuploidies in our study. Two recent studies analysed data on microarray‐CGH results in a large number of pregnancies undergoing prenatal invasive testing for a variety of reasons, such as maternal age >35 years, high risk from combined testing or second trimester serum screening, maternal request and others . In the group of pregnancies with a high risk from aneuploidy screening, the authors reported an overall incidence of copy number variations with known clinical significance or potential clinical significance of about 1%, which is similar to what was observed in our population (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…The couple also have a daughter with severe intellectual disability, while most of the daughter's cousins from the father's side have abnormal phenotypes. aCGH technique has an incremental yield over conventional cytogenetics of 0.9-1.6%, which has been mostly highlighted in cases of fetuses with structural defects [Papoulidis et al, 2015]. The use of aCGH was crucial for this case to delineate the exact genotype of the fetus and to coordinate genetic counseling.…”
mentioning
confidence: 99%